Potensi Marungga atau Kelor (Moringa oleifera L.) Lokal Nusa Tenggara Timur Sebagai Komoditas Pangan Fungsional - Noldy R E Kotta; Alfonso Sitorus (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Kotta NRE, Sitorus A. 2020. Potential of marungga or moringa (Moringa oleifera L.) local east Nusa Tenggara as a functional food commodity. In:Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Marungga or moringa is a source of functional food because it contains high nutrients and bioactive compounds. In ENT, there are two types of marungga, namely green and red marungga, which have been registered at the Center for Protection and Registration of Plant Varieties in 2019. The ENT Regional Government has compiled a Road map to develop marungga as a superior commodity. However, the development of marungga must be followed by optimal product utilization. Therefore, the purpose of writing this paper is to review marungga as a source of functional food so that people understand the importance of consuming marungga for health. This paper contains: 1) the physical characteristics of the red and green marungga from ENT; 2) The nutritional potential of marungga functional food; 3) Physiochemical properties of marungga; 4) Processed products of marungga as functional food. Based on the results of the review, marungga is a functional food commodity that is rich in functional bioactive compounds, such as phenolic acid, flavonoids, alkaloids, phytosterols, natural sugars, vitamins, minerals, and organic acids. These compounds make marungga have pharmacological properties such as anti-cancer, anti-diabetes, anti-inflammatory and antioxidant properties. If it is related to cases of malnutrition, ENThas the highest rate of malnutrition in Indonesia. So it is expected that the content of 40 essential nutrients in marungga can be used as complementary foods for malnutrition children.